2007
DOI: 10.1098/rsif.2007.1146
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of water by subunit c of ATP synthase

Abstract: We consider an ancient protein, and water as a smooth surface, and show that the interaction of the two allows the protein to change its hydrogen bonding to encapsulate the water. This property could have made a three-dimensional microenvironment, 3-4 Gyr ago, for the evolution of subsequent complex water-based chemistry. Proteolipid, subunit c of ATP synthase, when presented with a water surface, changes its hydrogen bonding from an a-helix to b-sheet-like configuration and moves away from its previous associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…the c-subunit ring, forms the pore of the mPTP (Alavian et al, 2014; Azarashvili et al, 2014). Purified, reconstituted c-subunit has been shown previously to form a channel with a diameter of 2.3 nm which allows molecules up to 1.5 kDa to pass, similar to PT (McGeoch & Guidotti, 1997; McGeoch et al, 2000; McGeoch & McGeoch, 2008). In agreement, our own electrophysiologic recordings of the purified mitochondrial c-subunit yield a multi-conductance, voltage dependent channel with prominent subconductance states.…”
Section: Evidence That the C-subunit Of Atp Synthase Creates The Highmentioning
confidence: 99%
See 1 more Smart Citation
“…the c-subunit ring, forms the pore of the mPTP (Alavian et al, 2014; Azarashvili et al, 2014). Purified, reconstituted c-subunit has been shown previously to form a channel with a diameter of 2.3 nm which allows molecules up to 1.5 kDa to pass, similar to PT (McGeoch & Guidotti, 1997; McGeoch et al, 2000; McGeoch & McGeoch, 2008). In agreement, our own electrophysiologic recordings of the purified mitochondrial c-subunit yield a multi-conductance, voltage dependent channel with prominent subconductance states.…”
Section: Evidence That the C-subunit Of Atp Synthase Creates The Highmentioning
confidence: 99%
“…When viewed from the inter-membrane space, the denuded c-subunit oligomer appears to have a central pore-like structure that is normally obscured by the F 1 stalk components, suggesting that the mouth of the pore may be unmasked by removal of F 1 (Pogoryelov et al, 2007). Although it has been suggested that phospholipids occupy the central cavity of the c-subunit ring in F 1 F O ATP synthases from different species (Oberfeld et al, 2006; Meier et al, 2001; Matthies et al, 2009) other evidence provides for formation of a proteolipid or proteophospholipid channel structure within the central lipid region upon activation of PT (Abramov et al, 2007; Elustondo et al, 2013; Azarashvili et al, 2014; McGeoch & McGeoch, 2008; Pavlov et al, 2005). Polyhydroxybutyrate (PHB) is a polymer distinct from the lipids that may form an ion channel within the lipid milieu if mammalian c-subunit is indeed filled with PHB (Elustondo et al, 2013; Pavlov et al, 2005).…”
Section: Structural Location Of the Pore Within The C-subunit Ringmentioning
confidence: 99%
“…Furthermore, the c-subunit had been shown previously to express ion channel activity [130]. As a matter of fact, the mammalian c-subunit undergoes conformational changes from an α-helix to a β-sheet when in contact with water, encompassing spaces that form the walls of ion channels [131]. These ion channels have a diameter of 2.3 nm which allows molecules up to 1.5 kDa to pass, similar to PT.…”
Section: The Mptp a Molecular Definitionmentioning
confidence: 99%
“…When viewed from the inter-membrane space, the denuded c-subunit oligomer appears as a ring with a central pore-like structure that is normally obscured by the F 1 stalk components gamma, delta and epsilon, suggesting that the pore may form within the center of the ring given the proper hydrophilic conformation [129]. Although it has been suggested that phosphlipids occupy the central cavity of the c-subunit ring in F 1 F O ATP synthases from different species [156158] other evidence provides for formation of a proteolipid or proteophospholipid channel structure within the central lipid region [58,62,118,131,159]. Data suggest a working model whereby the c-subunit pore forms within the proteolipid milieu upon activation of mPTP (for example by elevated matrix Ca 2+ ) whereupon the ring expands and F 1 shifts; the pore is closed by a decrease in diameter of the ring and inactivated by binding of the F 1 components to the ring (Figs.…”
Section: The Mptp a Molecular Definitionmentioning
confidence: 99%
“…The multilayer honeycomb ice-like model depicted in Figure 1, which has been recently proposed by Pollack and co-workers [12,19], seems to be consistent with the experimental evidence. It is worth recalling that water hexamers have been observed next to diverse surfaces, including metals [22,23], protein subunits [24], and graphene [25,26], as well as in supercooled water [27].…”
Section: Introductionmentioning
confidence: 99%